2018
DOI: 10.3390/ijerph15112579
|View full text |Cite
|
Sign up to set email alerts
|

Released Volatile Organic Compounds in Southern Yellow Pine before and after Heat Treatment

Abstract: As the main material in indoor furniture, southern yellow pine (Pinus spp.) releases volatile organic compounds (VOCs) into the environment during use. To better understand variations in the contents of VOCs in southern yellow pine before and after heat treatment, this study conducts dry heat treatment on southern yellow pine at 140 °C and 220 °C. Headspace solid phase micro-extraction was used to extract VOCs from southern yellow pine. The VOCs of southern yellow pine before and after heat treatment were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…wood, where the number of VOCs increased with heat treatment temperature, although the total VOC quantity emitted is decreased in thermally treated softwoods. There were 86, 93, and 131 VOCs identified in untreated specimens, specimens heat treated at 140°C, and specimens heat treated at 220°C, respectively (Wang et al 2018).…”
Section: Formation Of New Vocsmentioning
confidence: 98%
See 3 more Smart Citations
“…wood, where the number of VOCs increased with heat treatment temperature, although the total VOC quantity emitted is decreased in thermally treated softwoods. There were 86, 93, and 131 VOCs identified in untreated specimens, specimens heat treated at 140°C, and specimens heat treated at 220°C, respectively (Wang et al 2018).…”
Section: Formation Of New Vocsmentioning
confidence: 98%
“…Temperatures above 150°C alter the physical and chemical properties of wood permanently (Akgül et al 2007) and chemical changes of wood components lead to new products and byproducts, including VOCs that can be emitted from wood after the treatment. Most of the new (by-)products resulting from the degradation of wood polymers appear only above 200°C and are formed at treatment temperatures of 220°C and 230°C (Esteves and Pereira 2009;Poncsak et al 2009;Culleré et al 2013;Wang et al 2018). For example, decomposition temperature of hemicelluloses and cellulose are about 200 to 260°C and 240 to 350°C, respectively (Mayes and Oksanen 2003).…”
Section: Voc Emissions From Thermally Modified Woodmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Jiang et al [8] stated that caproaldehyde and pentaldehyde in wood VOCs were highly sensitive to temperature. In a preliminary study, it was found that the main VOC content of southern yellow pine samples decreased the most when heat treatment was conducted at 220 • C [9]. However, the energy consumption of heat treatment in the wood industry is high, and it can cause other drawbacks including the change of surface color and decrease of mechanical strength [10].…”
Section: Introductionmentioning
confidence: 99%